2016
DOI: 10.21037/gs.2016.11.04
|View full text |Cite
|
Sign up to set email alerts
|

Transoral endoscopic thyroidectomy vestibular approach (TOETVA) for Graves’ disease: a comparison of surgical results with open thyroidectomy

Abstract: Background: Transoral endoscopic thyroidectomy vestibular approach (TOETVA) provides excellent cosmetic results from its potential for scar-free operation. The procedure has been applied successfully for Graves' disease by the authors of this work and compared with the standard open cervical approach to evaluate its safety and outcomes.Methods: From January 2014 to November 2016, a total of 97 patients with Graves' disease were reviewed retrospectively. Open thyroidectomy (OT) and TOETVA were performed in 49 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
104
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(118 citation statements)
references
References 28 publications
3
104
2
9
Order By: Relevance
“…The technique will be described in brief in the technique section. Udelsman et al at reported a series of 7 cases of TOETVA (2 parathyroidectomy and 5 thyroidectomy) with no complications, which was the first series in the United (30). The operative time was longer in the TOETVA group.…”
Section: Oral Vestibular Approachmentioning
confidence: 99%
“…The technique will be described in brief in the technique section. Udelsman et al at reported a series of 7 cases of TOETVA (2 parathyroidectomy and 5 thyroidectomy) with no complications, which was the first series in the United (30). The operative time was longer in the TOETVA group.…”
Section: Oral Vestibular Approachmentioning
confidence: 99%
“…expanded this to include patients with Grave’s disease with at least one of the following: suspicious nodules, toxic multinodular goiter, failure or recurrence after 2 years of anti-thyroid medication, local compressive symptoms, and patients with side effects from anti-thyroid medication. Of note, all patients in this series were euthyroid at the time of the procedure (38). Each group’s inclusion criteria have been summarized in Table 1 (2225,27,36,3840).…”
Section: Indications and Inclusion Criteriamentioning
confidence: 91%
“…Of note, all patients in this series were euthyroid at the time of the procedure (38). Each group’s inclusion criteria have been summarized in Table 1 (2225,27,36,3840). …”
Section: Indications and Inclusion Criteriamentioning
confidence: 91%
See 2 more Smart Citations